A Wide-Proteome Analysis to Identify Molecular Pathways Involved in Kidney Response to High-Fat Diet in Mice - Dozio, Elena; Maffioli, Elisa; Vianello, Elena; Nonnis, Simona; Grassi Scalvini, Francesca; Spatola, Leonardo; Roccabianca, Paola; Tedeschi, Gabriella; Corsi Romanelli, Massimiliano Marco (International journal of molecular sciences, 2022)
The etiopathogenesis of obesity-related chronic kidney disease (CKD) is still scarcely understood. To this aim, we assessed the effect of high-fat diet (HF) on molecular pathways leading to organ damage, steatosis, and fibrosis. Six-week-old male C57BL/6N mice were fed HF diet or normal chow for 20 weeks. Kidneys were collected for genomic, proteomic, histological studies, and lipid quantification. The main findings were as follows: (1) HF diet activated specific pathways leading to fibrosis and increased fatty acid metabolism; (2) HF diet promoted a metabolic shift of lipid metabolism from peroxisomes to mitochondria; (3) no signs of lipid accumulation and/or fibrosis were observed, histologically; (4) the early signs of kidney damage seemed to be related to changes in membrane protein expression; (5) the proto-oncogene MYC was one of the upstream transcriptional regulators of changes occurring in protein expression. These results demonstrated the potential usefulness of specific selected molecules as early markers of renal injury in HF, while histomorphological changes become visible later in obesity-related CDK. The integration of these information with data from biological fluids could help the identification of biomarkers useful for the early detection and prevention of tissue damage in clinical practice.